Survei Tingkat Keberhasilan Belajar Menggunakan Metode Pembelajaran Mind Mapping Materi Lari Estafet Kelas XI SMAN 1 Rengasdengklok - Ahmad Mahirdo Holis; Nana Suryana N; Akhmad Dimyati (Peneliti.net, 2022)
Based on the results of observations at SMAN 1 Rengasdengklok on PJOK class XI subjects, it shows that student learning outcomes reach the completeness value set by the school. In PJOK learning, students usually look bored and seem monotonous even the material given is sometimes not easy for most students to memorize the material that has been given and if given questions about the material previously taught many students cannot answer. Therefore, the use of the Mind Mapping learning method in PJOK learning which is applied in the note model can help students more easily remember and understand the material given by the teacher. The goal to be achieved in this research is to find out how student learning outcomes in the PJOK subject matter for relay running after applying the Mind Mapping learning method. The subjects used were Class XI students of SMAN 1 Rengasdengklok, totaling 84 students. The research approach used is descriptive quantitative. The research data were obtained through tests using multiple choice questions, totaling 18 questions that had been tested for validity and reliability. The results showed that there were 86% of students who achieved the KKM and there were 12% of students who had not yet reached the KKM. So it can be concluded that the results of the study have met the standard of completeness from the school as much as 70%, therefore the data of students who have completed studying as much as 86% can be categorized as